Contributions to the Local Community Through the University - Maeshima, Shinichiro (IntechOpen, 2022)
Universities have two roles. As educational institutions, a university develops human resources with advanced expertise, and as research institutions, they promote the investigation of issues in researchers' specialized fields. In addition, the role of universities has recently expanded to include contributing to the local community. Universities should engage in social contributions by returning the knowledge acquired through their educational and research activities to the local community through related activities such as joint research and technology transfer as part of industry-academia-government cooperation, and improving the lives and welfare of local residents, leading to vitality and the formation of a prosperous society. This book describes the community contribution activities and social connections of our university since its establishment.